Do shareallocations to the indigenous investor drive the demand for IPOs? - Ahmad Hakimi Tajuddin; Kanesh Gopal Rajadurai; Rasidah Mohd-Rashid; Waqas Mehmood; Elkhan Sadik-Zada (Economies, 2023)
The purpose of this paper was to investigate the impact of allocating shares to the indigenous (Bumiputera) investors on the oversubscription ratio of IPO. This factor is unique to Malaysian IPOs and would enable us to reflect the signaling theory. Data on 348 IPO firms listed on Bursa Malaysia over a span of 17 years from 2002 to 2018 were examined using a cross-sectional regression analysis. The findings demonstrated no significant impact arising from the fractions of shares allocated to Bumiputera investors on the oversubscription ratios, except that the revised guidelines on the Bumiputera equity requirement had a significant negative influence on oversubscription. Further tests showed that the influence of such share allocation on oversubscription was moderated by firm size, which was proxied by market capitalization. The findings lend support to the signaling theory, indicating that the demand for IPOs will be slightly higher for larger firms listed in bigger markets.
Keywords: 330; indigenous; Bumiputera; IPO; oversubscription; signaling; firm size; retail investors